From Home to the Streets: Investigating the Patterns of Running Away from Home and the Push & Pull Factors of Street Children in Peshawar - Nasira Nasreen; Imran Ahmad Sajid, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the question: why children are on the streets in Peshawar? Street children are one of the ‘at risk’ categories of children as per national laws and international instruments. Literature reveals a complex interplay of push and pull factors contributing to the presence of children on the streets in Peshawar. This study was conducted on street children who were currently under the custody of state institutions in Peshawar. The study employed interviews of tools for data collection. All ethical protocols were followed. The study found a total of eighteen (18) factors (12 push and 6 pull) contributing for children to be on the streets of Peshawar. The study also shed light on patterns of running from home. The study informs the development of more effective interventions and policies to protect vulnerable children and facilitate their reintegration into safe and supportive environments within Peshawar, Khyber Pakhtunkhwa.